Phosphatidylserine Exposing Extracellular Vesicles in Pre-eclamptic Patients - Lalic-Cosic, Sanja; Dopsaj, Violeta; Kovac, Mirjana; Mandic-Markovic, Vesna; Mikovic, Zeljko; Mobarrez, Fariborz; Antovic, Aleksandra (Frontiers in Medicine, 2021)
Background: Pre-eclampsia (P-EC) is associated with systemic inflammation, endothelial dysfunction and hypercoagulability. The role of extracellular vesicles (EVs) in coagulation disturbances affecting the development and severity of P-EC remains elusive. We aimed to evaluate the concentration of EVs expressing phosphatidylserine (PS) and specific markers in relation to the thrombin and fibrin formation as well as fibrin clot properties, in pregnant women with P-EC in comparison to healthy pregnant women of similar gestational age. Methods: Blood samples of thirty pregnant women diagnosed with P-EC were collected on the morning following admission to hospital and after delivery (mean duration 5 days). The concentration of the PS-exposing EVs (PS+ EVs) from platelets (CD42a+), endothelial cells (CD62E+) and PS+ EVs expressing tissue factor (TF) and vascular cell adhesion molecule 1 (VCAM-1) were measured by flow cytometry. Further phenotyping of EVs also included expression of PlGF. Markers of maternal haemostasis were correlated with EVs concentration in plasma. Results: Preeclamptic pregnancy was associated with significantly higher plasma levels of PS+ CD42a+ EVs and PS+ VCAM-1+ EVs in comparison with normotensive pregnancy. P-EC patients after delivery had markedly elevated concentration of PS+ CD42a+ EVs, CD62E+ EVs, TF+ EVs and VCAM-1+ EVs compared to those before delivery. Inverse correlation was observed between EVs concentrations (PS+, PS+ TF+ and PlGF+) and parameters of overall haemostatic potential (OHP) and fibrin formation, while PS+ VCAM-1+ EVs directly correlated with FVIII activity in plasma. Conclusion: Increased levels of PS+ EVs subpopulations in P-EC and their association with global haemostatic parameters, as well as with fibrin clot properties may suggest EVs involvement in intravascular fibrin deposition leading to subsequent microcirculation disorders.